Identification of a Flavin Monooxygenase-Like Flavonoid 8-Hydroxylase with Gossypetin Synthase Activity from Lotus japonicus. (8th January 2021) - Hiraga, Yasuhide; Shimada, Norimoto; Nagashima, Yoshiki; Suda, Kunihiro; Kanamori, Tina; Ishiguro, Kanako; Sato, Yuka; Hirakawa, Hideki; Sato, Shusei; Akashi, Tomoyoshi; Tanaka, Yoshikazu; Ohta, Daisaku; et al.
Abstract: Lotus japonicus is a model legume that accumulates 8-hydroxyflavonol derivatives, such as gossypetin (8-hydroxyquercetin) 3- O -glycoside, which confer the yellow color to its petals. An enzyme, flavonoid 8-hydroxylase (F8H; LjF8H), is assumed to be involved in the biosynthesis, but the specific gene is yet to be identified. The LjF8H cDNA was isolated as a flavin adenine dinucleotide (FAD)-binding monooxygenase-like protein using flower buds and flower-specific EST data of L. japonicus . LjF8H is a single copy gene on chromosome III consisting of six exons. The conserved FAD- and NAD(P)H-dependent oxidase motifs were found in LjF8H. Phylogenetic analysis suggested that LjF8H is a member of the flavin monooxygenase group but distinctly different from other known flavonoid oxygenases. Analysis of recombinant yeast microsome expressing LjF8H revealed that the enzyme catalyzed the 8-hydroxylation of quercetin. Other flavonoids, such as naringenin, eriodictyol, apigenin, luteolin, taxifolin and kaempferol, also acted as substrates of LjF8H. This broad substrate acceptance was unlike known F8Hs in other plants. Interestingly, flavanone and flavanonol, which have saturated C–C bond at positions 2 and 3 of the flavonoid C-ring, produced 6-hyroxylflavonoids as a by-product of the enzymatic reaction. Furthermore, LjF8H only accepted the 2S -isomer of naringenin, suggesting that the conformational state of the substrates might affect product specificity. The overexpression of LjF8H in Arabidopsis thaliana and Petunia hybrida synthesized gossypetin and 8-hydroxykaempferol, respectively, indicating that LjF8H was functional in plant cells. In conclusion, this study represents the first instance of cloning and identification of F8Hs responsible for gossypetin biosynthesis.